Analisis Lama Perendalam Kedelai Terhadap Kualitas Tempe (Rasa, Warna, dan Tekstur) untuk Bahan Olahan Mendoan - Felisiana Fidelia; Melvitha Putri Prihanza; Nova Yulita; Uswatun Khasanah; Ipin Aripin (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The purpose of this study was to analyze the effect of soybean soaking time on the quality of tempeh as a mendoan ingredient, especially in terms of taste and texture. Mendoan tempeh has unique sensory characteristics that are largely determined by the quality of tempeh in the initial stages of processing, so that the soybean soaking process is an important factor that needs to be studied scientifically. The research method/approach used was an experimental method with a completely randomized design, where the treatment was a variation of soybean soaking time for 8 hours, 12 hours, and 16 hours. Data were obtained through organoleptic tests using a hedonic scale on the taste and texture of mendoan tempeh, involving untrained panelists, then analyzed using analysis of variance (ANOVA) with the help of SPSS software. The results of the study showed that variations in soybean soaking time had a significant effect on the quality of taste and texture of tempeh as a mendoan ingredient. The 12-hour soaking time produced the highest preference value for both sensory parameters compared to other treatments. The conclusion of this study confirms that controlling the soaking time of soybeans is a crucial initial stage in producing optimal quality tempeh for processed mendoan, and has the potential to become a technical reference for traditional food business actors in improving product quality.